Nitric oxide synthase inhibition and oxidative stress in cardiovascular diseases: Possible therapeutic targets? - Rochette, Luc; Lorin, Julie; Zeller, Marianne; Guilland, Jean-Claude; Lorgis, Luc; Cottin, Yves; Vergely, Catherine (Pharmacology & therapeutics (Oxford), 2013)
Nitric oxide (NO) is synthetized enzymatically from l-arginine (l-Arg) by three NO synthase isoforms, iNOS, eNOS and nNOS. The synthesis of NO is selectively inhibited by guanidino-substituted analogs of l-Arg or methylarginines such as asymmetric dimethylarginine (ADMA), which results from protein degradation in cells. Many disease states, including cardiovascular diseases and diabetes, are associated with increased plasma levels of ADMA. The N-terminal catalytic domain of these NOS isoforms binds the heme prosthetic group as well as the redox cofactor, tetrahydrobiopterin (BH(4)) associated with a regulatory protein, calmodulin (CaM). The enzymatic activity of NOS depends on substrate and cofactor availability. The importance of BH(4) as a critical regulator of eNOS function suggests that BH(4) may be a rational therapeutic target in vascular disease states. BH(4) oxidation appears to be a major contributor to vascular dysfunction associated with hypertension, ischemia/reperfusion injury, diabetes and other cardiovascular diseases as it leads to the increased formation of oxygen-derived radicals due to NOS uncoupling rather than NO. Accordingly, abnormalities in vascular NO production and transport result in endothelial dysfunction leading to various cardiovascular disorders. However, some disorders including a wide range of functions in the neuronal, immune and cardiovascular system were associated with the over-production of NO. Inhibition of the enzyme should be a useful approach to treat these pathologies. Therefore, it appears that both a lack and excess of NO production in diseases can have various important pathological implications. In this context, NOS modulators (exogenous and endogenous) and their therapeutic effects are discussed.